(æ)fter the storm: An Examination of the short-a system in Greater New Orleans. (March 2020) - Carmichael, Katie
Abstract: This study examines the short-a system in Greater New Orleans (GNO) following the demographic changes and large-scale displacement that occurred after Hurricane Katrina in 2005. I provide a linguistic description of the short-a systems of 57 residents of the GNO suburb of Chalmette, half of whom relocated after the storm, and half of whom returned to their pre-Katrina homes. While many speakers demonstrate robust split systems, analysis demonstrates a shift over time toward the nasal system common throughout much of the US. Whether participants returned or relocated was not a significant predictor of short-a system; however, speakers most oriented to places outside of Chalmette may have led the change in progress, pointing to the importance of considering place orientation in contexts of speaker mobility. This study establishes that adoption of the nasal system is well underway in GNO, generating further questions about what New Orleans English will sound like as post-Katrina changes continue to develop.